1995
DOI: 10.2307/1131790
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Coding Strategies of One-Year-Old Infants in a Locomotor Search Task

Abstract: The ability of 1-year-old infants to remember the location of a nonvisible target was investigated in 3 experiments. Infants searched for a toy hidden in one of many possible locations within a circular bounded space. The presence, number, and spatial arrangement of local cues or "landmarks" within this space were varied. The results of Experiment 1 showed that search performance was highly successful when a landmark was coincident with the location of the toy ("direct"), but less successful when a landmark wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 0 publications
3
53
0
1
Order By: Relevance
“…Nevertheless, between 6 and 12 months, infants begin to demonstrate that they are capable of orienting by using visual guidance strategies employing coincident or adjacent visual cues or landmarks (Acredolo, 1978;Acredolo & Evans, 1980;Bremner, 1978a,b;Bushnell, McKenzie, Lawrence, & Connell, 1995;Tyler & McKenzie, 1990). Between 6 and 12 months of age infants also begin showing that they can orient using path integration/dead reckoning (Acredolo, 1978;Acredolo, Adams, & Goodwyn, 1984;Rieser & Heiman, 1982), and, for example, can use closely related landmarks to visually identify a goal location after rotation and translation (Lew, Bremner, & Lefkovitch, 2000).…”
Section: Discussion -Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, between 6 and 12 months, infants begin to demonstrate that they are capable of orienting by using visual guidance strategies employing coincident or adjacent visual cues or landmarks (Acredolo, 1978;Acredolo & Evans, 1980;Bremner, 1978a,b;Bushnell, McKenzie, Lawrence, & Connell, 1995;Tyler & McKenzie, 1990). Between 6 and 12 months of age infants also begin showing that they can orient using path integration/dead reckoning (Acredolo, 1978;Acredolo, Adams, & Goodwyn, 1984;Rieser & Heiman, 1982), and, for example, can use closely related landmarks to visually identify a goal location after rotation and translation (Lew, Bremner, & Lefkovitch, 2000).…”
Section: Discussion -Experimentsmentioning
confidence: 99%
“…Previous studies have shown that by the second half of the first year (8.5 to 12 months) children are able to use visual guidance strategies (i.e., coincidental landmarks) to identify target locations (Acredolo, 1978;Acredolo & Evans, 1980;Bremner, 1978b;Bushnell et al, 1995;Lew et al, 2000). It was thus surprising that in Experiment 2 (4-location task), some children between 17 and 20 months of age failed to discriminate the reward location even in the presence of the local cue.…”
Section: Comparison With Previous Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that numerous researchers have observed better search accuracy when object location is coded by more, as opposed to less, distinctive cues (Brenmer, 1978a(Brenmer, , 1978bBushnell, McKenzie, Lawrence, & Connell, 1995;Butterworth et al, 1982;Cornell, 1981), this latter coding will thus produce poorer performance. A different concern with these studies is that the level of overall search accuracy across all experiments was not especially high; the average best case performance in any condition was approximately 67% correct.…”
Section: Discussionmentioning
confidence: 99%
“…Children older than 22 months were more accurate when indirect landmarks were visible, whereas the youngest children performed the same whether the landmarks were visible or not. These data suggested that toward the end of infancy children begin to use indirect landmarks to guide navigation (see also DeLoache and Brown, 1983;Bushnell et al, 1995).…”
Section: How Children Use Objects and Landmarksmentioning
confidence: 95%